Examining the role of patients' experiences as a resource for choice and decision-making in health care: a creative, interdisciplinary mixed-method study in digital health - Sue Ziebland; John Powell; Pamela Briggs; Crispin Jenkinson; Sally Wyke; Elizabeth Sillence; Peter Harris; Rafael Perera; Fadhila Mazanderani; Angela Martin; Louise Locock; Laura Kelly; et al. (NIHR Journals Library, 2016)
Background: Traditional health information has been based on facts and figures and not on patient experience (PEx). Websites featuring people's accounts of their experiences of health and illness are popular as a source of information, support and much else. However, there are concerns that experiential information on the internet might have adverse effects on health. Aims: To find out whether, when and how the NHS should incorporate PEx into online health information and elucidate the mechanisms through which PEx might influence health, develop a tool to measure the effects of online PEx, explore how PEx is used, and investigate the feasibility and acceptability of a randomised controlled trial of online PEx. Methods: Mixed methods, including a conceptual literature review, qualitative secondary data analysis, the development of a new questionnaire, online ethnography, observational and experimental studies in an internet café environment, and finally feasibility trials to compare new websites based on PEx with those based on facts and figures. Results: The review concluded that online PEx could affect health outcomes through seven domains (information, support, affecting relationships, providing ideas on how to use health services, influencing behaviour change, learning to tell the story and visualising illness). We developed the e-Health Impact Questionnaire, which demonstrates good psychometric properties and is suitable for use across different health groups and various styles of online information. Online ethnographic studies found three types of PEx on multiple sclerosis (MS) platforms: accounts of 'living with MS', self-expression and creativity, and experiences of health care and treatment. Observational and laboratory-based methods included studies of how people find and use PEx to inform health choices. We developed a three-stage model (gating, the engagement loop and outcomes) which guided the development of six prototype multimedia websites featuring either experiential information (intervention) or factual information (comparator) for three exemplar health issues. We evaluated the feasibility and acceptability of a trial of the prototype PEx websites, comparing self-report and process measures with a comparator. In the three conditions we randomised 87 (smoking cessation), 148 (asthma), and 42 (caring for someone with MS) participants. At final (2-week) follow-up, retention rates were 75%, 82% and 86%, for smoking cessation, asthma and MS carers, respectively. Usage of the allocated websites was low. The median number of logins to the websites over the 2-week period was two, two and four; the median number of page views was 10, 15 and 27.5, respectively, with a median total duration on site of 9 minutes, 17 minutes and 31.5 minutes respectively. There were no reported adverse events or harms. The qualitative interviews with 30 trial participants found that the trial methods were acceptable and not burdensome and that preferences for combinations of different types of information were both idiosyncratic and dependent on timing and need. Limitations: This programme used a pragmatic, mixed-methods approach, in which we adapted some standard approaches (e.g. realist review). The conceptual review provided a framework for the whole programme but did not draw on a single overarching theoretically informed approach. Instead, we used relevant theory and methods from the work package leads, who represented a range of disciplines. Conclusions: Online PEx is not seen as an alternative to facts, or to care from a health professional, but is used in addition to other sources of information, support and expression. This programme of work indicates how the sharing of online PEx may benefit people, and how this can be measured. A randomised controlled trial is feasible but an allocated 'exposure' to a 'dose of information' is far from from how online experiences are shared in everyday life. Future work evaluating online health interventions which incorporate personal experiences should aim to reflect 'natural' use of the internet and might include online ethnography and offline interviews. Studies might explore how and why people use online sources of experience-based health information, and the effects on subsequent behaviour and health and social outcomes in different conditions. Future intervention research evaluating online health interventions should examine and explain issues of engagement and use, and seek to identify how to increase engagement. Trial registration: Current Controlled Trials ISRCTN29549695. Funding: This project was funded by the Programme Grants for Applied Research programme and will be published in full in Programme Grants for Applied Research; Vol. 4, No. 17. See the NIHR Journals Library website for further project information.